The effect of preoperative supplementary parenteral nutrition on nutrition and inflammation in gastric cancer patients - Xiaoyan Huang; Changxing Cui; Jing Wang; Dongchi Kong; Yuanqing Cui; Peng Huang; Xuelong Li (Discover Oncology, 2024)
Abstract Objectives Supplemental parenteral nutrition (SPN) is recommended to add when enteral nutrition alone is not sufficient. This research aims to evaluate the effect of preoperative SPN in patients with gastric cancer. Methods A total of 180 patients with gastric cancer were divided into three groups (60 patients per group) according to different nutritional support scheme. The primary endpoint was the changes in nutrition and inflammatory, while the secondary endpoint included the changes in prognosis. Results Compared with the control group, there were significant differences in nutrition and inflammation related indicators in the oral nutrition supplement (ONS) group and the SPN + ONS group (P < 0.05). Compared with the ONS group, the SPN + ONS group showed significant differences in the above indicators (P < 0.05). However, no significant changes were observed in the incidence of complications, the postoperative exhaust time, and the hospitalization time. Conclusions Preoperative SPN had a positive effect on nutrition and inflammation of gastric cancer patients undergoing surgery, but had no significant effect on their prognosis.